Analysis of the setting and predictive factors of the effect of attack according to game ecology: the case of female volleyball - Rodrigues Rocha, A. C.; Ferreira Pedrosa, G.; Barreiros Freire, A.; Moreira Praça, G.; Ugrinowitsch, H.; de Oliveira Castro, H.; Teixeira Costa, G. (Kinesiology, 2020)
The objective of this study was to identify how the ecological variables influence the setter during the setting and what were the predictive factors of the attack effect among Brazilian teams ranked from the 1st to 4th place in the volleyball Women`s Super-League in 2016-2017. We analyzed 768 attacks from 10 matches played among the teams. A descriptive analysis was performed and, to identify how the setting location differed in relation to the ecological variables, the One-Way ANOVA (factor 1 = setting location) was used. In addition, multinomial logistic regression was performed to understand the predictive factors of the effect of the attack. The significance level was set at 5% (p=.05) and the SPSS software version 20.0 was used. The results showed the setting location differed according to the distance between the setter and the central attacker, the distance between the setter and the central blocker, and the distance between the setter and the blocker of position 4. Besides, it was observed that the powerful attack and the blocking touch were predictive factors of the effect of the attack. Thus, it is concluded that the decision-making for the action of the setting is based on the availability of the central attacker and the configuration of the blockers, the powerful attack reduces the chances of defense and the blocking touch reduces the chances of scoring by attacking.